MODEL DISCOVERY LEARNING SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Alfirdaus, Sinta Khoiriyah; Muallimin, Muallimin; Usriyah, Lailatul (STIT AL MULTAZAM, 2024)
The ability to think critically is needed by students in the learning process, especially in science learning. However, the reality shows that often students make mistakes in making decisions because of lack of understanding of concepts in learning materials and lack of critical thinking skills. The purpose of this study is to determine the effectiveness of the Discovery learning model as an effort to improve critical thinking skills in science learning in elementary / MI. The method applied in this writing is a literature study (library research) conducted by investigating various literature studies. The results of the analysis of several previous studies that have been analyzed show an increase in students' critical thinking skills after applying the discovery learning learning model. The analysis proves that the application of the discovery learning learning model in science learning in elementary schools has a positive impact on improving thinking skills.